LGBTQ+ EXISTENCE IN INDONESIA: INVESTIGATING INDONESIAN YOUTH’S PERSPECTIVES TOWARDS THE LGBTQ+ COMMUNITY - Ikrar Genidal Riadil (Faculty of Social and Political Sciences University of Bangka Belitung, 2020)
The presence of lesbian, gay, bisexual, transgender, and queer communities is a mandatory requirement. Even though the LGBTQ+ community is a group of people concerned about religious belief, Indonesians even now regard LGBTQ+ as transgression and sin. Those who do not consequently approve of same-sex marriage. Interestingly, this perception has been disputed because, in reality, others may have started to be open-minded and fully accept the prevalence of LGBTQ+ people in LGBTQ+ communities. This study used qualitative research to investigate the perspective of Indonesian younger generations towards the LGBTQ+ community in Indonesia. The researcher used the questionnaire as an instrument for data collection with ten questions required to fulfilled by Indonesian youth to investigate their perspectives. The study's data is collected from Indonesian participants, with a total of was eighty-three Indonesian youths between the ages of 15-26 in all around Indonesia. Since the issue of the study is quite sensitive in Indonesia, there are sure of positive and negative perspectives that are also apparent in the result of questionnaires. In a nutshell, the study's aim will further help the authorities take precautions to be incorporated in the future. Also, it is to investigate the Indonesian youths from a different background of beliefs and perspectives toward the LGBTQ+ community. The implication of this research informed young people of the LGBTQ+ subculture to Indonesian parents and teachers as those responsible for educating young kids so that they would not be adversely affected by this social phenomenon.